Analysis of ovaries in studies of reproduction in red deer (Cervus elaphus, L.): Application and limitations - Langvatn, Rolf (Rangifer, 1992)
A set of definitions for luteal structures and their regressing stages in red deer ovaries is suggested. Structural characteristics in ovaries pertaining to reproductive analysis is compiled from relevant literature and combined with observations from the present study. Luteal structures and their regressing stages may be useful in assessment of reproductive status and history, provided the analysis is performed with a full understanding of the limitations of the criteria and the methodological approach. Primary corpus luteum (PCL), corpus luteum of pregnancy (CLV), and corpus rubrum (CR) are the most important structures in the quantitative analysis of reproduction, and they may be identified at a macroscopic level. However, confusion with other structures is conceiveable, and for an accurate analysis microscopic -examination of histological preparations is necessary. Different processing and analysing procedures are compared, illustrating differences in resolution and precision, especially in retrospective analysis. Data from hinds with known reproductive history indicate limitations and potential in analysis of ovaries as a technique to assess reproductive status and history in red deer.
Keywords: Cervus elaphus; red deer; ovaries; analysis; luteal structures; definitions; histology; development; methods; accuracy